Empirical Analysis of Human Capital Convergence in Indonesia - Anwar, Aminuddin (Universitas Negeri Semarang, 2018)
This research analyzes the convergence hypothesis that applied to human capital which is one of important factor for economic development. This modelÃ‚Â appliedÃ‚Â to analyzeÃ‚Â the condition ofÃ‚Â provinces in Indonesia that have different conditions of human capital between regions for 33 provinces in Indonesia for two period between 2004 to 2010 and 2010 to 2016. This study uses data panels in estimating with fixed effects model as the best model choice. The result of the analysis for sigma convergence model is a decrease of global dispersion of human capital growth in Indonesia for the both periods. The results of beta convergence confirm the existence of absolute and conditional convergence model for the both periods. The determinants of human capital convergence in first period are economic growth, poverty, illiteracy, access to sanitation, access to clean water, number of health centers, and number of universities. Meanwhile different conditions are shown in the second period where the determinants of conditional convergence of human capital are determined only by economic growth, poverty, and sanitation access.